Thinking without limits: developing and validating a transdisciplinary thinking scale for Filipino students - Honra, Joelash R.; Monterola, Sheryl Lyn C. (Journal of Education and Learning (EduLearn), 2025)
Transdisciplinary thinking is crucial for addressing global challenges, yet standardized assessment tools for high school students are lacking. This study addresses this gap by developing and validating a transdisciplinary thinking scale (TTS) tailored for this demographic. Following established methodologies, the TTS was crafted through expert interviews, resulting in a 20-item scale. A pilot test with 402 senior high school students showed strong internal consistency (Cronbach’s Alpha=0.920) and a multidimensional structure: integrative thinking, inquiry skills, and collaborative problem-solving. The TTS supports existing models of transdisciplinary cognition, emphasizing it is multifaceted nature. This scale offers educators a reliable tool to assess and foster transdisciplinary thinking skills. Integrating TTS-informed pedagogies can better prepare students for the complexities of the 21st century, promoting integrative and collaborative problem-solving. Validating the TTS marks a significant advance in educational research, promoting integrative thinking essential for addressing contemporary challenges